Coupling analysis of penetrated wire connecting two electronic devices using a time domain hybrid method. Issue 9 (29th May 2021) - Ye, Zhihong; Lu, Changchang; Zhang, Yu
Abstract: An efficient time domain hybrid method is proposed, which integrate transmission line (TL) equations, finite‐difference time‐domain (FDTD) method, Norton and Substitution theorems together, to predict the EM fields coupling with the penetrated wire connecting two electronic devices. Within this method, the geometry of penetrated wire is divided into external and internal TLs according to the shielded enclosures of two devices firstly. Then the equivalent circuit model of penetrated wire is established by the Norton and Substitution theorems, which can represent the discontinuity of impedance between external and internal TLs and the transmitting of interference signals between terminal loads of the wire. Finally, the TL equations combined with FDTD method is utilized to compute the transient responses on external and internal TLs respectively. Numerical simulations of penetrated wire connecting two shielded enclosures in different environment are employed to verify the accuracy and efficiency of the presented method.